The operators - Hastings, Michael ([S.l.] : Orion Publishing Group, 2012)
General Stanley McChrystal, the innovative commander of international and US forces in Afghanistan, was living large. Loyal staff liked to call him a 'rock star'. During a spring 2010 trip across Europe to garner additional Allied help for the war effort, McChrystal was accompanied by journalist Michael Hastings of Rolling Stone. For days, Hastings looked on as McChrystal and his staff let off steam, partying and openly bashing the Obama administration for what they saw as a lack of leadership. When Hastings' piece appeared a few months later, it set off a political firestorm: McChrystal was ordered to Washington, where he was unceremoniously fired. In The Operators, Hastings gives us a shocking behind-the-scenes portrait of Allied military commanders, their high-stakes manoeuvres and often bitter bureaucratic in-fighting. He takes us on patrol missions in the Afghan hinterlands and to hotel bars where spies and expensive hookers participate in nation-building gone awry, drawing back the curtain on a hellish complexity and, he fears, an unwinnable war.
Keywords: Afghan War (2001-); Buddhism and politics; Hastings, Michael, 1980-2013; Military leadership; Military policy; United States; United States. Army; War on Terrorism (2001-2009)